DYSTOPIAN SOCIETY IN PETRICK NESS’ THE KNIFE OF NEVER LETTING GO - Rantih, Wiva Dwi; Sari, Dian Eka (STBA Prayoga Padang, 2023)
Abstract The dystopian society is a reflection of a bad social environment that happened in reality. In this study, the researcher has found three problems of study, the government control, the loss of Todd’s individual identity, and how discourse works in the novel The Knife of Never Letting Go. It uses the sociological theory by Michel Foucault and uses descriptive method to analyze the data. The concepts from Foucault such as panopticon that underlined the bounderies in society to human being’s freedom, it is going to be way to uncover the first and the second problem. By using the concept of discourse that influences choices and actions in society is used to uncover the third problem.